Analysis of Flouting Maxims in Dialogue of Doctor Strange Movie - Magdalena Ayu; Maydinda Ayu Puspitasari; Shinta Marnesa (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This research analyzes the flouting maxims based on the character' dialogue in the Doctor Strange movie (2016). Flouting the maxims also occurs in literary works such as films. It does not only happen in everyday conversation. Communication is otherwise the transmission of information from one person to another, but the information transmitted must be accessible to the recipient. Communication becomes when the actors create a discussion. The cooperative principle is divided into the four conversational maxims of Grice. There are four more specific maxims that Grice proposed, such as quantity, quality, relation, and manner. These four maxims describe particular principles observed in striving for effective communication by people who follow the cooperative principle. This research revealed what types of maxims were disregarded by the characters in the Doctor Strange (2016) movies.